The Concept of Leadership in Islamic Educational Institutions in Motivating Teaching and Educational Staff - Agesta Eka Salindri; M.Sirozi (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the concept of leadership of Islamic educational institutions in motivating educators and education staff. This study uses a qualitative approach with the method of literature study (library research), this study examines various sources of literature related to the concept of leadership of Islamic Educational Institutions in motivating educators and education. Based on the results of the study, it is very important for leaders to apply things to motivate their staff such as, providing an understanding of individual needs or aspirations, open or transparent communication, providing appreciation, providing professional development opportunities, creating a positive work environment, as well as setting clear and measurable goals, facilitating teamwork, and evaluating constructive feedback so that they will be able to motivate their ranks to work more effectively, efficiently, and productively, but also to create a positive and sustainable work culture. Success in motivating staff will contribute to improving the quality of education provided to students and enhancing the reputation of the institution in society.